Correlation between ITGB2 expression and clinical characterization of glioma and the prognostic significance of its methylation in low-grade glioma(LGG) - Liu, He; Wang, Jiao; Luo, Tao; Zhen, Zhiming; Liu, Li; Zheng, Yalan; Zhang, Chaobin; Hu, Xiaofei (Frontiers in Endocrinology, 2023)
This study aimed to determine the biomarker value of ITGB2 expression or methylation in patients' survival and prognosis with LGG. We studied the expression of ITGB2, methylation, and immune significance of LGG patients' OS through bioinformatics analysis. According to TCGA, Rembrandt, CGGA database, ITGB2 can be a potential marker for mesenchymal molecular subtype gliomas. COX regression analysis shows that ITGB2 is an independent predictive marker of OS in malignant glioma patients. Biological processes show that ITGB2 has involved glioma immune-related activities, especially closely related to B cells CD4+Tcells, macrophages, neutrophils, and dendritic cells. ITGB2 is negatively regulated by ITGB2 methylation, resulting in low expression in LGG tissues. Low expression of ITGB2 and high methylation indicate good OS in patients with LGG. The ITGB2 methylation risk score (ITMRS) obtained from the ITGB2 methylation CpG site can better predict the OS of LGG patients. Thus, ITGB2 may be a promising biomarker of prognosis and may play an essential role in the process of immune cell infiltration.